Grazing ecology and forest history - Vera, F. W. M.; Vera, F. W. M. (Wallingford :CABI Publishing, 2000)
It is a widely held belief that a climax vegetation of closed forest systems covered the lowlands of Central and Western Europe before man intervened in prehistoric times to develop agriculture. If this intervention had not taken place, the forest would still be there, and if left the grassland vegetation and fields now present would revert to a natural closed forest state, although with a reduced number of wild species. This book, which an updated and expanded version of the author's 1997 thesis (presented to the Wageningen University, Netherlands), challenges the traditional view, using examples from history, pollen analyses and studies on the ecology of tree and shrub species such as oak and hazel. It tests the hypothesis that the climax vegetation is a closed canopy forest, against the alternative hypothesis that species composition and vegetational succession were governed by large herbivores, and that the Central and Western European lowlands were covered by a park-like landscape consisting of grasslands, scrub, solitary trees and groves bordered by a mantle and fringe vegetation. Comparative information from the eastern USA is also included throughout the book (this was not present in the thesis), because the forests there are commonly regarded as being analogous to the primeval vegetation in Europe. The book is arranged in 7 chapters: (1) General introduction and formulation of the problem; (2) Succession, the climax forest and the role of large herbivores; (3) Palynology, the forest as climax in prehistoric times and the effects of humans; (4) The use of the wilderness from the Middle Ages up to 1900; (5) Spontaneous succession in forest reserves in the lowlands of Western and Central Europe - including examples from France, Germany, Austria, Slovenia, Sweden, Poland; (6) Establishment of trees and shrubs in relation to light and grazing; and (7) Final synthesis and conclusions. Twelve appendices are included giving further information, and there are 67 pages of references and a subject index.
Keywords: BB500 - History and Biography; BB700 - Palaeontology and Archaeology; KK100 - Forests and Forest Trees (Biology and Ecology); KK600 - Agroforestry and Multipurpose Trees: Community, Farm and Social Forestry; PP300 - Land Resources; PP350 - Grasslands and Rangelands; PP700 - Biological Resources (General); PP720 - Biological Resources (Plant); ZZ331 - Plant Ecology; ZZ332 - Animal Ecology; Austria; Central Europe; Europe; France; Germany; Poland; Slovenia; Sweden; USA; Western Europe